Laboratory performance evaluation of porous asphalt mixture containing recycled concrete aggregate and fly ash - Asad Elmagarhe; Qing Lu; Mohammed Alamri; Mohammad Alharthai; Ahmed Elnihum (Case Studies in Construction Materials, 2024)
This study performed laboratory experiments to evaluate the performance of porous asphalt mixtures (PAMs) containing recycled concrete aggregate (RCA). One open aggregate gradation with Class C fly ash as the filler, granite aggregate, two binder types (PG 67–22 and PG 76–22), and four RCA contents (0%, 10%, 20%, and 30% by mass of aggregates in the sieve size range of 4.75 to 9.5 mm) were included in the experiments. The mixture properties evaluated include permeability and air-void content, Marshall stability and flow, indirect tensile strength, moisture susceptibility, Cantabro abrasion loss, macrotexture, and sound absorption coefficient. The study found that using a blend of granite and RCA in a PAM led to better performance in terms of indirect tensile strength, stiffness, moisture resistance, and resistance to raveling. This was particularly confirmed for PAMs with an unmodified PG 67–22 binder. The mixture that contained 30% RCA performed the most satisfactorily, with an indirect tensile strength of 0.81 MPa and a Marshall stability of 23 kN at 25 °C. These values were 37.5% and 15%, respectively, higher than the control mixture. Based on these results, the study recommends the use of 30% RCA in PAMs for the friction course of a highway pavement or the porous surface of a porous pavement.